ANALISA PENGENDALIAN KECEPATAN MOTOR DC MENGGUNAKAN PENGENDALI HYBRID SMC DAN PID DENGAN METODE HEURISTIK - Dian Mursyitah (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
Sliding Mode Control (SMC) is a controller which is famous for robustness to interference. However, SMC has a weakness that is chattering. On the application chattering can causes a large error steady state on the system. The magnitude of the steady state error can lead to instability. To solve these problems, the addition of a PID controller is required to lower the error steady state to a minimum, because there is an integral control to eliminate the steady state error. Thus, combining both controllers can increase the capabilities of each controller. Based on the simulation results for DC motor speed control using hybrid SMC and PID controllers obtained good performance. Proven to achieve setpoint, robust to interference with the minimum steady state error and stability are maintained with a fast response time is 0,0657 second and ess = 20,1%